Concentration of exporting brazilian wooden doors - Oliveira, Gustavo Silva; da Silva, Maycon Thuan Saturnino; Novack Junior, Nilton Sérgio; Lambert, Luciano; Soares, Philipe Ricardo Casemiro; Atanazio, Kemely Alves (Scientia Agraria Paranaensis, 2017)
<span style="font-family: 'Helvetica',sans-serif; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">This study aimed to analyze the evolution of Brazilian wood doors exports in the period 2005-2015, as to their concentration. Monetary values of exports were collected in the UNCONTRADE database and deflated (base year 2005). For determine the concentration, it used the methods of Herfindahl-Hirschman and the concentration ratio (CR2, CR4 and CR8) classified in the Bain criteria. The real value of Brazilian exports doors for the reporting period decreased from US$ 227.3 million in 2005 to US$ 154.3 million in 2015. The analysis of the concentration of Brazilian exports doors, by Hirschman Index-Herfindahl the period 2005-2009, showed a fall of market concentration ranging from 0.4626 to 0.2829 in the meantime. According to the criterion of Bain, the concentration was deemed too high. Thus, it was observed that there are still opportunities to be exploited by Brazilian companies, to expand the market to other countries.